2019
DOI: 10.1101/572636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In search of Universal Cortical Power Changes Linked to NMDA-Antagonist based Anesthetic Induced Reductions in Consciousness

Abstract: B. Abstract Background. Despite their intriguing nature, investigations of the neurophysiology of N-methyl-D-aspartate (NMDA)-antagonists Xenon (Xe) and nitrous oxide (N2O) are limited and have revealed inconsistent frequency-dependent alterations, in spectral power and functional connectivity. Discrepancies are likely due to using low resolution electroencephalography restricted to sensor level changes, concomitant anesthetic agent administration and dosage. Our intention was to describe the effects of equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Likewise, Ballesteros et al found a gradual increase in high beta, low gamma power in ventral premotor cortex, S1, and secondary somatosensory cortex (Ballesteros et al, 2020). Although there are no mesoscopic LFP spectral data with N 2 O, previous spectral analyses with EEG data show that N 2 O can increase and decrease high-frequency power (Yamamura et al, 1981;Rampil et al, 1998;Foster and Liley, 2011;Pelentritou et al, 2019). We found increased high-frequency (>20-45 Hz) power in motor cortex within beta and gamma bands.…”
Section: Time-frequency Dynamicssupporting
confidence: 70%
“…Likewise, Ballesteros et al found a gradual increase in high beta, low gamma power in ventral premotor cortex, S1, and secondary somatosensory cortex (Ballesteros et al, 2020). Although there are no mesoscopic LFP spectral data with N 2 O, previous spectral analyses with EEG data show that N 2 O can increase and decrease high-frequency power (Yamamura et al, 1981;Rampil et al, 1998;Foster and Liley, 2011;Pelentritou et al, 2019). We found increased high-frequency (>20-45 Hz) power in motor cortex within beta and gamma bands.…”
Section: Time-frequency Dynamicssupporting
confidence: 70%
“…Various electroencephalographic and magnetoencephalographic studies in humans have reported spectral, functional connectivity, and complexity changes associated with nitrous oxide (5)(6)(7)(8)(9)(10), but at sedative rather than psychedelic concentrations or without assessment of psychedelic phenomenology. Although there has been investigation of the effect of nitrous oxide on cerebral blood flow using magnetic resonance imaging (MRI) (11), there have been no functional MRI (fMRI) studies during nitrous oxide exposure in humans that have characterized changes in functional brain networks associated with psychedelic effects.…”
Section: Introductionmentioning
confidence: 99%